A review of the discussions on cultivated meat from the Islamic perspective - Mohammad Naqib Hamdan; Rufaihah Abdul Jalil; Mohd Anuar Ramli; Nasiibah Ramli; Mohd Nor Adzhar Ibrahim; Muhamad Firdaus Ab Rahman; Hussein ‘Azeemi Abdullah Thaidi; Nur Najwa Hanani Abd Rahman (Heliyon, 2024)
Since the introduction of the cultivated meat burger in 2013, numerous discussions have transpired between researchers and consumers, manifesting in various forms such as academic publications, opinions on personal websites and interactions on social platforms. For Muslim consumers, a primary concern revolves around the halal status of cultivated meat, given the pivotal role of adhering to a halal diet as a divine obligation in their lives. Therefore, this article seeks to systematically review the existing literature on cultivated meat from an Islamic perspective as articulated by Muslim scholars, whether these perspectives are issued by an established fatwa organisation or representations of personal views. The sources incorporated into this analysis span from academic publications, newspaper articles, fatwa bodies, personal websites and interviews. Employing thematic analysis, five principal themes were discerned within the discourse among Muslim scholars regarding cultivated meat: (i) the ontological status of cultivated meat, (ii) the status and source of stem cells used in the cultivation process, (iii) the theological implications of cultivated meat production on altering God's creation, (iv) foundational principles for halal cultivated meat production, and (v) the contemporary necessity of cultivated meat from the perspective of al-maqasid al-shariah. It is duly recommended that international fatwa organisations such as the International Islamic Fiqh Academy (IIFA) engage in discussions and deliberations on this matter of growing significance within the food industry. The fatwas and resolutions issued by IIFA are frequently cited as the most recognised authority in many Islamic countries.